Details of the Latina Nagara (mono-spired) Shikhara - Temples of India Project Team (Jio Institute, 2024)
Details of the Latina Nagara (mono-spired) shikhara (superstructure) above the main garbhagriha (sanctum sanctorum) of the Suswani Mata Temple. The corner bands termed as the venukosha are composed of small aedicules placed in diminishing heights, divided by thin ribbed discus or amalaka. The discus looks like beaded bands. The aedicules have ribbed corners and diamond motifs on the front faces.